An Online Latin Poetry Translation Lab in an Italian Classical High School - Landi, Licia (IALLT Journal of Language Learning Technologies, 2003)
This paper is an account of a project on the strategy for technologybasedcourse development and management adopted for teachinga 4th -year Latin poetry class in an Italian Oassical High school. Itfocuses on a strategy for course design, online delivery, and integrationwith an e-mail discussion list. The examples focus on Latinpoetry, and there is a discussion of how technology can couple withchanges in pedagogy and increase learning productivity, even intraditional subjects, when learners become self-motivated, selfdirected,and collaborative participants in their learning experience.